Climate Change and Food Security - Piacentini, Ruben Dario Narciso (2019)
Climate change resulting in global warming has a massive adverse effect onthe production of foods of all kind. The first chapter discusses this matter inconsiderable detail. It is clear that it is essential to follow practices that willminimize greenhouse gas emissions in order to secure food supplies. Thechapter on diet explains why plant-based foods are much more sustainableand indeed healthier choices. Increased consumption of plant based foods willreduce strain on resources. Indeed, new sources of nutritious foods areneeded. Much interest has appeared in including a wide variety of insects asa source of proteins. Furthermore, as all foods are perishable and subject tomicrobial degradation it is necessary to devise ways of mitigating such loss.Indeed, wastage of food at various stages of its production, processing,storage as well as consumption is a critical factor in influencing the potential of food insecurity. It is impossible to eliminate waste but it is possible tominimize it. These topics are covered in some depth in this book in a series ofchapters. The importance of drying technology in the areas of preservation,storage and transportation of various goods has already been mentioned.Various dryer types and their applications relevant to food security arediscussed in a separate chapter.